Group training programs and self-reported injury risk in female marathoners - Parker, D. T.; Weitzenberg, T. W.; Amey, A. L.; Nied, R. J. (Clinical Journal of Sport Medicine, 2011)
Objective: To investigate the association of group training program (GTP) participation and other known risk factors with training and intrarace injury rates in female marathoners.